Pelatihan Pembuatan Website Pembelajaran Menggunakan Google Site Learning Website Development Training Using Google Site: Learning Website Development Training Using Google Site Learning Website Development Training Using Google Site - Endaryono Endaryono; Mahyudi Mahyudi; Aswin saputra; Indra Kurniawan (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Working and studying from home is a demand that must be done at this time, since the Covid-19 pandemic due to the Corona virus. Schools were closed, teaching and learning activities were transferred online at home. Due to these demands, many teachers and parents are required to start adapting to distance learning activities, using technology. Bridging this, Google Indonesia launched the Teaching from Home initiative. Google provides a special website for teaching and learning activities for school students, in the Indonesian version. With this facility, anyone, including teachers, can create internal project hubs, team sites, publicly displayed sites, and more. Everything is done without the help of designers, programmers and IT. With the new Google Sites, creating a site is easy. This training is intended for teachers who are still not clear and looking confused how to create Google Sites to support distance learning between teachers and students to make it more interesting and fun.